Treatment of Psychotic Depression with Combination Olanzapine/Sertraline - Canavan, Neil (MD Conference Express, 2008)
Results from the National Institute of Mental Health’s Study of the Pharmacotherapy of Psychotic Depression [STOP-PD] were presented at the American Psychiatric Association’s 2008 Annual Meeting. To investigate the efficacy of a pharmacotherapeutic approach, STOP-PD looked at monotherapy with an antipsychotic versus an antipsychotic/antidepressant combination.